Kekayaan Perairan Teluk Hol dan Pantai Sulamadaha yang Berpotensi sebagai Daya Tarik Wisata di Kota Ternate - Fitria Soamole (Tekstual, 2018)
Sulamadaha beach is an object of interest to tourist that as administration located inSulamadaha Village, Ternate city of North Molucas . Sulamadaha beach gives attractions ofthe tourism nature such as beautiful of surface the sea and in the world sea.The mind of this research is to describe the potentials of the object interest tourism InThe Holl of Sulamadaha Beach. Descriptive method is used in this research because it todescribe the potentials of the object interest tourism. In this research used qualitative methodto analyze. The collecting data in this research is recording the informant likes government,tourist and observation.The result of this research applied that water in Holl of Sulamadaha had the beautyand unique of surface the sea and in the world sea. Surface the likes the nature panorama, theview of the sea, coral, fish and kindÃ‚Â  of marine biota that show of the potential of the sea